Comparison of Sound Attributes of Multichannel and Mixed-Down Stereo Recordings - Maurycy J. KIN; Przemysław PLASKOTA (Archives of Acoustics)
The work presents a comparison of some sound attributes perceived at a multichannel and stereo playback of musical recordings. The width of the virtual source, coherence impression, total size of sound scene, general quality and balance were the subjects of interest after the format reduction in accordance with the ITU recommendation. The results showed that evaluation of these attributes depends on the way the original audiosphere has been created in the surround system, for example, for a narrow virtual source the mix-down process causes only a small change in its size but for a broad source the observed degradation is significant. In addition, different ways of conversion from the multichannel to stereo format have been tested for compatibility.